Proteasome inhibitors as experimental therapeutics of autoimmune diseases - Verbrugge, Sue Ellen; Scheper, Rik J; Lems, Willem F; de Gruijl, Tanja D; Jansen, Gerrit (Arthritis research & therapy, 2015)
Current treatment strategies for rheumatoid arthritis (RA) consisting of disease-modifying anti-rheumatic drugs or biological agents are not always effective, hence driving the demand for new experimental therapeutics. The antiproliferative capacity of proteasome inhibitors (PIs) has received considerable attention given the success of their first prototypical representative, bortezomib (BTZ), in the treatment of B cell and plasma cell-related hematological malignancies. Therapeutic application of PIs in an autoimmune disease setting is much less explored, despite a clear rationale of (immuno) proteasome involvement in (auto)antigen presentation, and PIs harboring the capacity to inhibit the activation of nuclear factor-κB and suppress the release of pro-inflammatory cytokines such as tumor necrosis factor alpha and interleukin-6. Here, we review the clinical positioning of (immuno) proteasomes in autoimmune diseases, in particular RA, systemic lupus erythematosus, Sjögren’s syndrome and sclerodema, and elaborate on (pre)clinical data related to the impact of BTZ and next generation PIs on immune effector cells (T cells, B cells, dendritic cells, macrophages, osteoclasts) implicated in their pathophysiology. Finally, factors influencing long-term efficacy of PIs, their current (pre)clinical status and future perspectives as anti-inflammatory and anti-arthritic agents are discussed.